Come rain or come shine ebook - Karon, Jan (Mitford, 2015)
#1 New York Time bestselling author Jan Karon delivers the wedding that millions of Mitford fans have waited for. It’s a June day in the mountains, with more than a few creatures great and small, and you’re invited—because you’re family.   Over the course of ten Mitford novels, fans have kept a special place in their hearts for Dooley Kavanagh, first seen in At Home in Mitford as a barefoot, freckle-faced boy in filthy overalls.   Now, Father Tim Kavanagh’s adopted son has graduated from vet school and opened his own animal clinic. Since money will be tight for a while, maybe he and Lace Harper, his once and future soul mate, should keep their wedding simple.   By the way, it’s a pretty casual affair, so come as you are and remember to bring a tissue or two. After all, what’s a good wedding without a good cry?